1998
DOI: 10.1016/s0014-5793(98)00930-2
|View full text |Cite
|
Sign up to set email alerts
|

GTP analogue hydrolysis by the Gs protein: implication for the role of catalytic glutamine in the GTPase reaction

Abstract: Hydrolysis of GTP, bound to members of the Gprotein superfamily, terminates their downstream signaling activity. A conserved glutamine serves a critical role in this pivotal guanosine triphosphatase (GTPase) reaction. However, the role of the catalytic glutamine in GTP hydrolysis is still not well understood. We have employed substrate-assisted catalysis to probe the catalytic mechanism of Gscx using GTP analogues. These GTP analogues, each having different functional groups, were designed to support or refute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
12
2
Order By: Relevance
“…In conclusion, it appears that the benzoyl group has some effect on the phosphoryl transfer reaction but that the most important contribution comes from the aromatic amine group. Following an earlier suggestion (14,26) and from this study, it appeared plausible that the aromatic amino group of DABP-GTP would, at least partially, substitute for the loss of function of the carbonamide side chain of Gln61, which is involved in stabilization of the transition state but possibly also in increasing the nucleophilicity of the water molecule.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In conclusion, it appears that the benzoyl group has some effect on the phosphoryl transfer reaction but that the most important contribution comes from the aromatic amine group. Following an earlier suggestion (14,26) and from this study, it appeared plausible that the aromatic amino group of DABP-GTP would, at least partially, substitute for the loss of function of the carbonamide side chain of Gln61, which is involved in stabilization of the transition state but possibly also in increasing the nucleophilicity of the water molecule.…”
Section: Resultssupporting
confidence: 66%
“…1; Table 1) is increased as compared with monoaminobenzophenone-GTP and phenylene-monoamine-GTP but is lower than DABP-GTP, suggesting that the benzoyl group does contribute to the rate acceleration. This is different from with G␣, where the benzoyl group has no effect on the cleavage rate (26). Hydrolysis resistance of monoaminobenzophenone-GTP and phenylene-monoamine-GTP underscores the critical role of the aromatic amino group as a catalytically functional group (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The latter notion has gained impetus by recent reports showing for the fi rst time that oncogenic Ras mutants can be chemically inactivated and are not irreversibly damaged in their capability to act as molecular switches. The defective GTPase reaction of different oncogenic mutants of Ras could be increased by up to three orders of magnitude by using a modifi ed GTP analog, 3,4-diaminobenzophenone-phosphoramidate-GTP (DABP-GTP [114,115]), instead of GTP [63]. The structures of DABP-GppNHp bound to Pro12 and Val12 mutants of Ras have shown that the DABP moiety is accommodated close to a hydrophobic patch of Pro12 or Val12 in the P-loop.…”
Section: Rasgapsmentioning
confidence: 99%
“…In other analogues, phosphate groups were introduced at the 5′-position with the aim of targeting P2 receptors, 9 G proteins (in the case of a guanosine 5′-triphosphate analogue) 10 or enzymes involved in purine metabolism (such as IMP dehydrogenase). 11 The structures of (N)-methanocarba purine analogues (5-12) synthesized for testing in binding and other biochemical assays are shown in Table 1.…”
mentioning
confidence: 99%